Abandonment of grazing in a mediterranean grassland area: consequences for ant assemblages - Azcárate, Francisco M.; Peco, Begoña (Insect Conservation and Diversity, 2012)
1. Abandonment of traditional activities in the rural areas is widespread in the developed world, and in the case of grazing, it is known to have negative consequences on the diversity of plant communities. Few studies have examined the impact of grazing abandonment on fauna, which in the case of ants is of considerable interest, given their usefulness as an indicator for monitoring environmental change. 2. Here, we present the results of a study conducted in Mediterranean grasslands of central Spain. Using pitfall traps, ants were sampled from 10 40 m· 20 m plots; ﬁve of them located in grazed systems and ﬁve in abandoned grazing systems. Descriptors used for the ant assemblage were ant species composition, ant species richness, ant functional groups, and subguilds of granivores. We used a seed bait test to discriminate between granivorous and non-granivorous ant species. 3. Our results show that abandoned grazing systems have more ant species and more heterogeneous ant assemblages. Changes in ant species composition and ant functional groups are more pronounced in habitats where woody encroachment progresses more rapidly (i.e. dry sectors and tree islands). Specialised granivores have reduced importance in the same habitat types. Conversely, facultative granivores increase their presence in abandoned grazing systems. 4. The increased functional and species ant diversity observed with grazing abandonment can be explained by the generation of a more heterogeneous environment at the smaller scales, in spite of being more homogenous at the larger scales, because the latter are less signiﬁcant for the organisms studied
Keywords: ant functional groups; Ants; Granivory; grazing abandonment; mediterranean grasslands